2021
DOI: 10.15586/qas.v13i2.837
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity mechanism of Ochratoxin A

Abstract: Mycotoxins, such as Ochratoxins, are widely distributed in nature and are common contaminants of human foodstuffs. Ochratoxins are a group of mycotoxins produced by a wide range of molds. Ochratoxin A (OTA), the most prominent member of this toxin family, is produced by various Aspergillus and Penicillium species. OTA is frequently found in foods such as cereals, oleaginous seeds, coffee, and meat products. This mycotoxin has been described as teratogenic, genotoxic, carcinogenic, and immunotoxic, and has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 87 publications
(107 reference statements)
1
24
0
Order By: Relevance
“…3 ). Localization to these organ systems is consistent with numerous studies which have, likewise, reported targeting of OTA to liver, kidney and intestines in other animal models including both presence and toxicity in these systems 32 34 , as well as several recent studies which have reported both distribution of OTA in multiple regions of the brain, and corresponding neurobehavioral effects 35 37 . The observed pattern of distribution is, furthermore, conspicuously aligned with an established role of organic anion-transporting polypeptides (OATP, i.e., SLCO superfamily) and organic anion transporters (OAT, i.e., SLC22A superfamily) in the cellular uptake of OTA 38 40 , which have been shown to be primarily localized to liver, kidney, intestine and brain in the zebrafish 41 , 42 .…”
Section: Resultssupporting
confidence: 88%
“…3 ). Localization to these organ systems is consistent with numerous studies which have, likewise, reported targeting of OTA to liver, kidney and intestines in other animal models including both presence and toxicity in these systems 32 34 , as well as several recent studies which have reported both distribution of OTA in multiple regions of the brain, and corresponding neurobehavioral effects 35 37 . The observed pattern of distribution is, furthermore, conspicuously aligned with an established role of organic anion-transporting polypeptides (OATP, i.e., SLCO superfamily) and organic anion transporters (OAT, i.e., SLC22A superfamily) in the cellular uptake of OTA 38 40 , which have been shown to be primarily localized to liver, kidney, intestine and brain in the zebrafish 41 , 42 .…”
Section: Resultssupporting
confidence: 88%
“…In cereal as well as forage grass stands, the amounts of mycotoxins depend on the dominant species in the sowed mixture [23]. The most commonly occurring mycotoxins are deoxynivalenol (DON), zearalenone (ZEN), aflatoxins (AF), T-2 toxin, and ochratoxin [24][25][26]. Additionally, the "Green Deal" and multiple studies point to the fact, that occurrence and amounts of mycotoxins contaminating the biomass are changing due to climate change [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…These health concerns in humans as well as animals widely affect animal production in the Czech Republic. It is important to note that, apart from the refusal of contaminated feed by animals, a non-negligible increase in expenses on veterinary treatments occurs as well, due to acute and chronic toxicosis [16,24,[35][36][37][38]. This shows a high need for field studies focused on mycotoxins in fodder.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are natural fungal contaminants common in a wide diversity of food products (De Souza et al., 2021; Heshmati et al., 2021; Jafari et al., 2021; Bangar et al, 2022; Mokhtarian et al., 2020). Mycotoxins can increase liver, bladder, lung cancer risk, infections, risk of several forms of cancer, asthma and arthritis, neurological problems, and mental depression (Batrinou et al., 2020; Deng et al., 2020; Grumi et al., 2020; Nourbakhsh and Tajbaksh, 2021; Pires et al, 2022; Mir et al., 2021). The application of ozone is one of the most promising strategies for inactivating mycotoxins, protecting food and beverage against mycotoxins, and reducing off‐odors or contaminants (Mostashari et al., 2021; Yang et al., 2021).…”
Section: Application Of Ozone In the Vineyards And Wineriesmentioning
confidence: 99%
“…It is widely established that the presence of Ochratoxin A (OTA) in wine is associated with fungal infection in the vineyards; moreover, the presence of Aspergillus section Nigri varieties is present on the surface of fresh berries and is associated with OTA contamination of grapes. OTA is a potential human carcinogen agent with teratogenic, immunogenic, nephrotoxic, and genotoxic features (Chain et al., 2020; Nourbakhsh & Tajbakhsh, 2021). Many surveys have investigated the presence of mycotoxins in wine and other processed grape products.…”
Section: Application Of Ozone In the Vineyards And Wineriesmentioning
confidence: 99%